Critical success factors of malaysian small and medium-sized enterprises in food and beverage manufacturing industry - Lee, Chun Hui (2017)
Although more studies focused on strategic management in SMEs recent years, exploration on successful small and medium-sized enterprises (SMEs) remains scarce. It is evident in the literature that SMEs especially those operating in food and beverage (F&B) manufacturing industry facing many challenges and obstacles to be successful and how SMEs succeed in the F&B manufacturing industry has remained a black box. This research suggests the critical success factors (CSF) approach in answering the broad research question of this study, how do SMEs in F&B manufacturing industry achieve success? Thirteen research questions are formulated to aid the answering of the broad research question. This study employed multiple case study methodology. Based on purposive sampling, this study selected 10 SMEs based on six selection criteria. These include continuous profitability and growth rate exceeding 10% for at least five consecutive years, the owners are satisfied with the SMEs financial and non-financial performance, and perceived the firm as top performers or market leaders, and lastly, the interviews with owners and top management are allowed. This study achieved data triangulation through collecting data through in-depth interviews, company documents, and direct observations during case visits. The researcher completed individual case reports before conducting within-case and cross-case analyses. In this study, all 10 SMEs identified three to five CSFs individually. Nevertheless, these SMEs achieve success with different combinations of CSFs. This research identified 18 CSFs from 10 cases, namely, value differentiation strategy, cost leadership strategy, human resource management, innovation, networking, effective quality management system, effective food safety management system, financial management, entrepreneurial orientation, business experience, integrated supplier management, entrepreneurial competencies, Halal accreditation, business diversification, attractive product packaging, flexible manufacturing system, high online visibility and effective foreign worker management. The study reaffirmed some of the CSFs investigated in previous studies while Halal accreditation, business diversification, attractive product packaging, flexible manufacturing system, high online visibility and effective foreign worker management are CSFs that emerged from the case studies. The study concludes that CSFs among successful F&B manufacturing SMEs in this study are multidimensional and complex in which SMEs have different approaches in the same CSF and each CSF led to success different ways. This research implies that CSF is a useful approach to understand the strategic management of successful SMEs in F&B manufacturing industry and suggest researchers and practitioners focus on these identified CSFs to improve competitiveness and business performance. Although the findings may be criticized because they are based on 10 companies, the study gained robust and in-depth insights into the CSFs of the F&B manufacturing SMEs through theoretical saturation and replication logic. The researcher suggests further research on the development of a new measurement instrument based on current findings. Also, this study recommends some future research directions, which includes longitudinal research on CSFs of F&B manufacturing SMEs, the comparison between successful and less successful SMEs, cross-sectional study in other industry, and further research on the impact of individual CSFs identified from this study in other industries.